A Therapeutic Renaissance - Emerging Treatments for Atopic Dermatitis - Chan Ho Na; Wenelia Baghoomian; Eric L. Simpson (Medical Journals Sweden, 2020)
Atopic dermatitis (AD) is a chronic, inflammatory cutaneous disease that is characterized by complex immune dysregulation and skin barrier dysfunction with a wide variety of clinical phenotypes. Until recently, conventional therapeutic modalities for AD remained rather non-specific despite AD's complex etiology. Failing to take into account the underlying inflammatory pathways led to treatments with inadequate efficacy or unacceptable long-term toxicities. We are currently in the midst of a therapeutic renaissance in AD. Recent progress in molecular medicine provides us a better understanding of the AD pathogenesis, suggesting a dominant helper T cell (Th) 2/Th22 response with a varying degree of Th1/Th17 overexpression. Targeted therapeutic agents including biologics and small molecule inhibitors in development hold promises for more effective and safer therapeutic approaches for AD. A better understanding of individual differences amongst AD patients will allow for a more tailored approach in the future. This review aims to cover the most promising emerging therapies in the field of atopic dermatitis utilizing recently published manuscripts and up-to-date conference abstracts and presentations.